Exposure to electromagnetic waves for reducing brain health: A bibliometric analysis - Savitri, Ida Ayu Gede Winda; Adnyana, I Made Dwi Mertha; Wahyudi, I Wayan; Dewi, Gusti Ayu Putu Wahyu Purnama; Ariastuti, Indria; Sundari, Ni Luh Putu Ari; Nuartha, Pande Komang Aditya Ryan (Svāsthya: Trends in General Medicine and Public Health, 2024)
Exposure to electromagnetic waves has been reported to have an adverse impact on human brain health. Various claims have revealed the impact of long-term exposure to electromagnetic waves clinically and nonclinically, but there are no comprehensive studies that explain the effects of electromagnetic wave exposure on human brain health.  This study aimed to identify the effects of electromagnetic wave exposure on human brain health. Using a meta-synthesis approach and bibliometric analysis. A total of 271 articles from Scopus, Web of Science and PubMed were screened to obtain 148 terms and analyzed descriptively. The findings from 2004–2024 articles that met the selection criteria resulted in 10 major clusters, 903 networks and 4,020 network strengths. The terms "1800 MHz mobile phone”, "900 MHz”, "acute exposure”, "assessment”, "behavior”, "bioeffect”, "biological effect”, "biological tissue”, "blood brain barrier”, "cell phone radiation”, "cellular phone”, "cellular telephone”, "central nervous system”, "child”, "chronic exposure" and others were most studied. Increased use of electronic devices and wireless technology significantly affects information processing and storage; disrupts synaptic communication and neuronal signaling; causes cognitive decline; disrupts the integrity of the blood‒brain barrier; and causes hypersensitivity through disruption of monoamine neurotransmitter metabolism, decreased dopamine levels, norepinephrine and epinephrine levels, 5-hydroxytryptamine "serotonin", excitatory amino acid neurotransmitters and acetylcholine esterase (AChE). The increased use of electronic devices and wireless technology significantly affects brain performance and health. Thus, it is important to minimize the effects of exposure to electromagnetic waves.